2012
DOI: 10.1177/0003319712467224
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score for the Prediction of Contrast-Induced Nephropathy in Elderly Patients Undergoing Percutaneous Coronary Intervention

Abstract: We developed a risk score for contrast-induced nephropathy (CIN) in elderly patients (n = 668) before percutaneous coronary intervention (PCI). Another 277 elderly patients were studied for validation. Based on the odds ratio, risk factors were assigned a weighted integer; the sum of the integers was the risk score. Among the 668 elderly patients, 105 (15.7%) experienced CIN. There were 9 risk factors for CIN (with weighted integer): estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m(2) (4), diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 31 publications
6
68
1
4
Order By: Relevance
“…The results of the present study are in agreement with the most results obtained by others reports Kato et al and Mehran et al [19][20][21][22][23][24][25][26][27]. In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the present study are in agreement with the most results obtained by others reports Kato et al and Mehran et al [19][20][21][22][23][24][25][26][27]. In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-).…”
Section: Discussionsupporting
confidence: 93%
“…In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-). This result is consistent with Wang et al, Liu et al and Nozue et al founded serum level of cystatin C is a reliable marker for CIN at 24 hours p<0.001 and serum creatinine increased significantly at 48 hours, also study carried by Wacker-Gussmann et al [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] found that cystatin C level and the cystatin C/creatinine ratio independently predict the risk of CIN in patients undergoing coronary angiography, but another study by Ribichini et al [32] found a significant increase in serum cystatin C concentrations 12 hours earlier than serum creatinine, therefore a rise of serum cystatin C at 12 hours from baseline was the earliest predictor of CIN than serum creatinine [18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Apesar da alta incidência de NIC, como ocorre nesse tipo de amostra (cateterismo urgente por IAM), podemos identificar características "protetoras" da amostra para a ocorrência de NIC, tais como: idade média bem abaixo de 75 anos; baixo volume infundido de contraste (em nosso estudo a média de volume infundido foi de 137,3 ml, bem abaixo dos cut offs de risco na literatura: para alguns > 200 ml 16 e para outros > 300 ml 12 ); média baixa de creatinina sérica na admissão com apenas quatro pacientes com creatinina sérica maior do que 2 mg/dL, o que impediu comparações de valor estatístico entre pacientes com creatinina menor e igual versus maior do que 2 mg/ dL (limite de creatinina que costuma ser utilizado como de risco para NIC); poucos pacientes com ICPP prévia; tempo médio de isquemia inferior a 6 horas. ICPP prévia e tempo de isquemia superior a seis horas foram fatores de risco em estudos anteriores.…”
Section: Resultsunclassified